Attosecond x-ray transient absorption in condensed-matter: a core-state-resolved Bloch model. (15th April 2019) - Picón, A; Plaja, L; Biegert, J
Abstract: Attosecond transient absorption is an ultrafast technique that has opened the possibility to study electron dynamics in condensed matter systems at its natural timescale. The extension to the x-ray regime permits one to use this powerful technique in combination with the characteristic element specificity of x-ray spectroscopy. At these timescales, the coherent effects of the electron transport are essential and have a relevant signature on the absorption spectrum. Typically, the complex light-driven dynamics requires a theoretical modeling for shedding light on the time-dependent changes in the spectrum. Here we construct a semiconductor Bloch equation model for resolving the light-induced and core-electron dynamics simultaneously, which enables to easily disentangle the interband and intraband contributions. By using the Bloch model, we demonstrate a universal feature on attosecond x-ray transient absorption spectra that emerges from the light-induced coherent intraband dynamics. This feature is linked to previous studies of light-induced Fano resonances in atomic systems.